2017
DOI: 10.1177/1078155217718382
|View full text |Cite|
|
Sign up to set email alerts
|

Retrospective comparison of low molecular weight heparin vs. warfarin vs. oral Xa inhibitors for the prevention of recurrent venous thromboembolism in oncology patients: The Re-CLOT study

Abstract: Background There is increasing evidence indicating oral factor Xa inhibitors can be used for secondary prevention of venous thromboembolism. Studies are needed to compare oral factor Xa inhibitors, low molecular weight heparins, and warfarin in the oncology population. The purpose of this study is to evaluate the recurrent venous thromboembolism incidence in oncology patients utilizing oral Xa inhibitors, low molecular weight heparins, or warfarin. Methods Using retrospectively collected data, we compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…In the present cohort, recurrence rate in both groups was about 4%, and no significant inter-group difference was found for symptomatic recurrence. The present recurrence rate was consistent with the 4%–15% recurrence rates reported in previous studies 616182728…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present cohort, recurrence rate in both groups was about 4%, and no significant inter-group difference was found for symptomatic recurrence. The present recurrence rate was consistent with the 4%–15% recurrence rates reported in previous studies 616182728…”
Section: Discussionsupporting
confidence: 93%
“…A recently published study demonstrated that rivaroxaban and edoxaban for cancer-associated VTE was not inferior to LMWH in terms of recurrence and major bleeding but increased clinically relevant bleeding 1314. Additionally, available research data support the administration of rivaroxaban to patients with cancer-associated VTE 15161718. However, there was no definitive study of the stability and therapeutic efficacy of rivaroxaban in gastrointestinal and pancreatobiliary cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to our predefined criteria, a total of 4 articles and 667 patients were included in the final analysis [ 8 , 9 , 11 , 12 ] (Flow Diagram). The majority of included articles (3 out of 4) were published in 2017.…”
Section: Resultsmentioning
confidence: 99%
“…VTE recurrence rates were also lower for rivaroxaban users than for warfarin users at 6 months (13.2 vs. 17.5%; p = 0.014) and 12 months (15.7 vs. 19.9%; p = 0.017) [HR 0.74, 95% CI (0.56-0.96); p = 0.028], with similar rates of major bleeding. Other studies have found that DOACs are at least as safe and effective as LMWH [47][48][49][50][51][52][53].…”
Section: Treatment Of Venous Thromboembolic Diseasementioning
confidence: 97%